Central Bank Interest Rate Policy in The Context of The Financial Crisis ("Journal "U". Economy. Management. Finance.", 2021)
The article considers the interest rate policy as the main instrument of monetary regulation in the state. This is a policy of direct influence on the money and credit market through direct and indirect methods. These include changes in interest rates, refinancing rates, setting interest rate corridors, open market operations, and others. The article defines these mechanisms and features of their use in crisis conditions by central banks of Russia and developed countries. The international experience of financial recovery is presented.
Keywords: interest rate policy; discount rate; refinancing rate; central bank; monetary regulation; financial crisis; interest rate corridor